Effect of positional isomers on the photochromic behaviors of bipyridyltriazolium chloroantimonate hybrids. Issue 14 (18th March 2020) - Shen, Jun-Ju; Kang, Xiao-Li; Ren, Qiao-Zhen; Li, Guo-Ping; Gao, Ya-Na; Hao, Peng-Fei; Fu, Yun-Long
Abstract : Two chloroantimonates with isomeric bipyridyltriazoliums exhibit distinct photochromic behaviors, of which 1 is the first reported photochromic chloroantimonate hybrid. Abstract : Two chloroantimonate hybrids with isomeric bipyridyltriazoliums and similar packing patterns, {[2-bpt]2 [(SbCl5 )Cl2 ]} n (1 ) and {[4-bpt]2 [(SbCl5 )Cl2 ]} n (2 ) (2-bpt 2+ = protonated 3, 5-bis(pyridine-2-yl)-1, 2, 4-triazole, 4-bpt 2+ = protonated 3, 5-bis(pyridine-4-yl)-1, 2, 4-triazole), have been designed and synthesized. Distinct intermolecular electronic interactions and photochromic behaviors are attributed to the remarkable modulation of positional isomeric effect on the electron deficiency of the acceptors and donor–acceptor matching relationship. 1 is the first reported photochromic chloroantimonate hybrid.